Pemanfaatan Lingkungan Sekitar Sebagai Media Pembelajaran Pada Mata Pelajaran IPS untuk Meningkatkan Hasil Belajar Peserta Didik di MI Islamiyah 1 Surowono Badas Kediri - Mega Dwi Susanti (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
problem in this research is the low teaching method used in MI Islamiyah 1 Surowono, Canggu, Badas, Kediri. Therefore, researchers strive to improve the activities and learning outcomes of learners by using the surrounding environment as a learning medium. Utilization of the surrounding environment as a learning medium for social sciences to improve the learning outcomes of learners in class V MI Islamiyah 1 Surowono, Canggu, Badas, Kediri has increased from cycles I, II and III by looking at the percentage. Data after the implementation of the utilization of the surrounding environment as a learning medium always shows a significant improvement. Classically, student learning outcomes increased from 61.11% to 88.88% in the second cycle. This means that the completeness of IPS learning by applying the utilization of the surrounding environment in cycle I, cycle II and cycle III has always increased and has reached the researcher's target of 85%.